Examining Student Motivation: Intrinsic Willingness or Parental Coercion in the Use of Icebreakers - Setiowati, Handriani Mutiasih; Adi, AB Prabowo Kusumo; Ardini, Sukma Nur (Universitas Pendidikan Mandalika, 2025)
Students study at a course is out of their personal will, yet due to coercion of their parents. Demonstrating icebreakers is highly suggested in non-formal education as establishing a pleasurable and refreshing atmosphere is the most critical aspect. This study investigates icebreakers as a method of fostering students' interest in BBC-English Training Specialists in Semarang. The objectives are to examine the role of instructorsÂ in fostering students' interest in a course, to examine how instructors adhere to the well-designed outline for implementing icebreaker methods, and to determine the advantages and disadvantages of this method. This study employed a qualitative method by incorporating narrative inquiry into the research design. The data were collected using an open-ended questionnaire, and four senior instructors were interviewed. The result of this study shows that the instructor's role in fostering students' interest is crucial. Meanwhile, the study has proven that implementing icebreakers in line with a well-designed outline successfully fosters students' interest in attending English courses and raises their awareness of the importance of learning English independently, free from parental coercion. There are virtually no disadvantages, hence it is highly suggested that the icebreaker method be used. This study allows instructors to create engaging, interactive, and productive activities according to the students' preferences. This makes it possible to adjust their methods to the unique needs of their students while also keeping up with the rapidly evolving educational landscape.